Phenoconversion of CYP2C9 in epilepsy limits the predictive value of CYP2C9 genotype in optimizing valproate therapy. (June 2015) - Tóth, Katalin; Bűdi, Tamás; Kiss, Ádám; Temesvári, Manna; Háfra, Edit; Nagy, Andrea; Szever, Zsuzsa; Monostory, Katalin
Aim : Since prominent role in valproate metabolism is assigned to CYP2C9 in pediatric patients, the association between children's CYP2C9-status and serum valproate concentrations or dose-requirements was evaluated.Materials & Methods : The contribution of CYP2C9 genotype and CYP2C9 expression in children (n = 50, Caucasian) with epilepsy to valproate pharmacokinetics was analyzed.Results : Valproate concentrations were significantly lower in normal expressers with CYP2C9*1/*1 than in low expressers or in patients carrying polymorphic CYP2C9 alleles. Consistently, the dose-requirement was substantially higher in normal expressers carrying CYP2C9*1/*1 (33.3 mg/kg vs 13.8–17.8 mg/kg, p < 0.0001). Low CYP2C9 expression significantly increased the ratio of poor metabolizers predictable from CYP2C9 genotype (by 46%).Conclusion: Due to the substantial downregulation of CYP2C9 expression in epilepsy, inferring patients' valproate metabolizing phenotype merely from CYP2C9 genotype results in false prediction.